Study on the Bending Behavior of the Double-Span Prestressed Steel Reinforced Concrete Beams - Habiera-Waśniewska, Elżbieta; Bodzak, Przemysław; Witkowski, Włodzimierz (Wydawnictwo Politechniki Łódzkiej, 2025)
The article deals with double-span, double composite beams, in which prestressed concrete is connected to a specially prepared rigid steel profile and in which their interaction with monolithic concrete is assumed. The paper describes the behavior of multi-span elements under loading, defines the term of plastic hinges in composite prestressed structures and explains the phenomenon of internal force redistribution. These issues are discussed in relation to the authors' own research. A computational analysis is then carried out, in which a nonlinear layer model of cross-section is formulated, based on the elastic-plastic characteristic of the materials used. The results show that there exists the local redistribution in tested elements, despite the discontinuity of the part of reinforcement in the middle-span zone. The degree of this interaction depends on the amount of reinforcement in the support section, the proper anchorage of that reinforcement and sufficient bond between the reinforcement and the concrete.
Keywords: double-span elements; steel reinforced concrete beams; global and local redistribution of forces